(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
One of the main dangers of improper weight loss is dehydration, which can lead to impaired organ function, decreased endurance, and cognitive decline. In addition, rapid weight loss is often accompanied by loss of muscle mass, which can weaken the strength and endurance of a fighter. Deficiency of essential nutrients can lead to weakened immunity, increased fatigue, digestive disorders, and hormonal disruptions. It is also possible to develop eating disorders, such as anorexia or bulimia, which create additional psychological problems. All of these factors can negatively affect an athlete’s athletic career and overall health. Purpose: to conduct an analytical analysis of publications in the PubMed web database dedicated to the problem of weight loss in martial arts using the VOSviewer software tool. To create a sample of studies as of 01.01.2025, bibliometric analysis of PubMed database data was used. The phrase «weight loss in martial arts» was used for the search. The analysis of publications was carried out from 1990 to 2024. The VOSviewer 1.6.19 program was used: keyword analysis method and direct citation analysis with the construction of bibliometric maps, visualization of cluster density and citation weight. 148 publications were removed using the VOSviewer 1.6.19 program. During the research period, 584 authors from 307 organizations were found. The most popular authors are: Franchini E. (9 publications), Real R. (9), Drid P. (6), Nakaji S. (6), Umeda T. (6), Bianco A. (5), Trivic T. (5), Sugawara K. (5). The program found 603 keywords (elements). For better analysis, a threshold of 2 was specified. 201 elements were selected for network visualization. They were grouped into 8 clusters. The main body of scientific publications is aimed at developing programs for weight loss and gain without negative consequences on the sports career and general health of athletes in various types of martial arts. The overlay visualization shows that most keywords with the newest publication dates (shown in yellow) characterize narrower concepts (sweating problem, weight control before competitions, rapid weight gain after weighing), while older publications are devoted to broader research (the impact of weight loss on the physical fitness and health of martial artists, development of a dietary program for athletes of various martial arts). Solving these problems should become a priority scientific direction in further research.